VD_FINDINFO Arrêt / 2014 / 632 vom 21. August 2014 - VD Tribunal cantonal (2014)
PC, DOMICILE, DOMICILE À L'ÉTRANGER, CENTRE DE VIE, DEVOIR DE COLLABORER | 23 al. 1 CC, 10 LPC, 4 LPC, 9 LPC, 13 LPGA, 43 LPGA, 61 let. c LPGA